Bayesian Persuasion in Coordination Games - Goldstein, Itay; Huang, Chong (American Economic Review, 2016)
We analyze a coordination game of regime change where the policy maker, who tries to increase the probability of the survival of the regime, commits ex ante to abandon the regime automatically when its fundamentals are below a certain threshold. This policy acts as an information transmission mechanism: agents, who decide whether to attack the regime or not, update positively about the fundamentals of the regime when they see that it has not been abandoned, and so they are less likely to attack. Using the commitment ability, the policy maker can thus increase the overall survival probability of the regime.